Alkylimidazolium Protic Ionic Liquids: Structural Features and Physicochemical Properties. Issue 4 (18th January 2022) - Shmukler, Liudmila E.; Fedorova, Irina V.; Fadeeva, Yuliya A.; Gruzdev, Matvey S.; Safonova, Liubov P.
Abstract: We focus on a series of protic ionic liquids (PILs) with imidazolium and alkylimidazolium (1R3HIm, R=methyl, ethyl, propyl, and butyl) cations. Using the literature data and our experimental results on the thermal and transport properties, we analyze the effects of the anion nature and the alkyl radical length in the cation structure on the above properties. DFT calculations in gas and solvent phase provide further microscopic insights into the structure and cation‐anion binding in these PILs. We show that the higher thermodynamic stability of an ion pair raises the PIL decomposition temperature. The melting points of the salts with the same cation decrease as the hydrocarbon radical in the cation becomes longer, which correlates with the weaker ion‐ion interaction inthe ion pairs. A comparative analysis of the protic ILs and corresponding ILs (1R3MeIm) with the same radical (R) in the cation structure and the same anion has been performed. The lower melting points of the ILs with 1R3MeIm cations are assumed to result from the weakening of both the ion‐ion interaction and the hydrogen bond. Abstract : The decomposition temperature of the protic ionic liquids (PILs) is directly proportional to the thermodynamic stability of their ion pairs. The decomposition temperature increases with decreasing difference in the anion and base proton affinity in the gas phase. The melting points of the PILs with the same anion decrease as the hydrocarbon radical in the alkylimidazolium cation becomes longer, which correlates with the weaker ion‐ion interactions.